Об'єктивність і правда в журналістиці - Михайлин, I.Л. (Культура народов Причерноморья, 2007)
The main principle of journalism is truth, not objectivity. Truth criterion is fairness perceived as observance of moral standard common to all mankind and orientation on an ideal of full national development.